2017
DOI: 10.21675/2357-707x.2017.v8.n1.888
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade Infantil Em Uma Capital Do Nordeste Brasileiro

Abstract: Objetivo: descrever a ocorrência da mortalidade infantil em Teresina (PI). Metodologia: estudo epidemiológico, descritivo, com dados secundários extraídos do Datasus, em que a população foi composta por todos os óbitos infantis, cujas mães são residentes em Teresina, no período de 2005 a 2014. Resultados: apesar das flutuações, houve declínio dos coeficientes de mortalidade neonatal, pós-neonatal e infantil. Houve predomínio de óbitos infantis em mães com idade entre 20 e 29 anos, e com escolaridade entre oito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
2
0
3
Order By: Relevance
“…The early period of neonatal life, the first 24 hours of life in particular, is the primary determining factor of infant mortality (57.1%). (8) Correlations between mode of delivery and maternal level of education in this study revealed higher rates on cesarean section among women with 12 years of education or more. Riscado et al, (24) also reported higher rates of cesarean section among women with higher socioeconomic status, higher levels of education, and access to private health care, suggesting this procedure is influenced by market trends.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The early period of neonatal life, the first 24 hours of life in particular, is the primary determining factor of infant mortality (57.1%). (8) Correlations between mode of delivery and maternal level of education in this study revealed higher rates on cesarean section among women with 12 years of education or more. Riscado et al, (24) also reported higher rates of cesarean section among women with higher socioeconomic status, higher levels of education, and access to private health care, suggesting this procedure is influenced by market trends.…”
Section: Discussionmentioning
confidence: 49%
“…Brazil is making progress in that area, but has yet to reduce these deaths before 2030. (8) The Metropolitan Region of São Paulo (RMSP -Região Metropolitana de São Paulo) is an important Brazilian region due to its high population density, social inequality and urban complexities. Public policies implemented in the last decades, especially health policies, must rely on data and indicators to effectively inform programs and actions aimed at better quality of life.…”
Section: ❚ Introductionmentioning
confidence: 99%
“…8 A redução da mortalidade infantil no Brasil encontra-se relacionada à melhoria nas condições de vida e na atenção à saúde da criança, como na alimentação e nutrição, saneamento básico, imunização e na mudança do modelo de atenção à saúde. 9,2 Muitos estudos relacionam a redução da mortalidade infantil à mudança no modelo de atenção baseado na saúde da família, o qual trouxe pontos positivos para a atenção à saúde da criança, [10][11] como ações intersetoriais, acesso universal com escuta qualificada e resolutividade das necessidades de saúde. 10 Os resultados deste estudo demonstram que, no período estudado, houve um decréscimo no CMI, e, também, nos componentes neonatal e pós-neonatal.…”
Section: Discussionunclassified
“…1 Internacionalmente, na maioria dos países, a mortalidade infantil está em declínio. 2 Segundo projeções do IBGE, no Brasil e no Estado do Piauí, as taxas de mortalidade seguem a mesma tendência mundial. No primeiro, essa taxa diminuiu de 30/1.000 nascidos vivos em 2000 para 13,82/1.000 nascidos vivos em 2015.…”
Section: Introductionunclassified
“…Somada à redução das internações por CSAP, houve um declínio da taxa de mortalidade infantil, o que também pode estar correlacionado com o aumento do acesso aos serviços primários em saúde (11). Entretanto, mesmo com a redução considerável da taxa de mortalidade infantil, quando se compara a países mais desenvolvidos, ainda transparece a necessidade de melhorias (12).…”
Section: Introductionunclassified